VALIDITAS MEDIA PEMBELAJARAN TIGA DIMENSI BOLA LAPISAN BUMI UNTUK MENINGKATKAN MINAT BELAJAR SISWA: Validity Of Three-Dimensional Learning Media Ball Layers Of The Earth To Increase Students' Interest In Learning - Sari, Chika Ameta; Nisa`, Siti Khoirotun; Putri, Meutia Revana Cahya; Marshelyna, Mela; Masfuah, Siti (Yayasan Al-Amin Qalbu, 2024)
This research is part of development research which aims to test the validity of the three-dimensional learning media of the earth's layers in the material about getting to know our earth on students' learning interest. The subjects of this research were two teachers and four fifth grade elementary school students who provided validation sheets to the teachers and questionnaire instruments to the students. Next, the data was analyzed quantitatively descriptively. Based on data analysis, the data obtained shows that the average percentage of indicators of student interest in learning is 59.37%, which is included in the category of high interest in learning. In essence, this media is valid and suitable for use in the learning process.